How digital fabrication can enable new methods in the architectural practice? - Silva, D. (2021)
Design methods have always changed, considering that design thinking is bound to the representational medium. Thus, its scope can be expanded by the enlarged possibilities offered by the new media and methodologies. Today, the computational methods are a crucial medium for architectural design. Not only digital media is augmenting our design capacity in profound ways, but also digital fabrication is establishing itself as a core discipline for architecture. It has the power to link digital design information with physical production processes, thus opening the opportunity to materialize ideas, experiments and investigate physical or digital artifacts during the design process.